Electrodeposition preparation and optimization of fan-shaped miniaturized radioisotope thermoelectric generator. (1st March 2020) - Xu, Zhiheng; Li, Junqin; Tang, Xiaobin; Liu, Yunpeng; Jiang, Tongxin; Yuan, Zicheng; Liu, Kai
Abstract: In view of the current energy demand for miniaturized equipment in extreme environmental fields, such as in deep space exploration. A new fan-shaped radioisotope thermoelectric generator is innovatively presented and designed. Thin-film thermoelectric materials used for miniaturized radioisotope thermoelectric generators are first prepared by electrochemical methods. The prepared fan-shaped radioisotope thermoelectric generator has a volume of 5.75 cm 3 and consists of 8 thermoelectric modules and 32 thermoelectric legs. The study finds that when a 1.5 W heat source is loaded, the temperature difference of the device is 54.8 K, the output voltage and the maximum output power is 174.88 mV and 333.20 nW, respectively. On this basis, the number and size of the modules are optimized by the finite element method. When the thermoelectric leg size is optimized to 9 × 2 mm 2 and the number of modules is 8, the maximum output power can be up to 369.02 nW. The corresponding experimental verification work is further developed and discussed. This work provides a novel solution for the energy supply problem of small-volume devices in extreme space environments. Highlights: A fan-shaped radioisotope thermoelectric generator (RTG) is fabricated. Flexible thermoelectric legs contribute to highly integrated miniature RTGs. Optimizing the size of the TE leg can increase the output power by more than 8%. The volumetric specific power of the miniature RTG can reach 59.38 nW/cm 3 . The power density of such miniature thermoelectric devices can reach 230.64 nW/g.